2014
DOI: 10.1002/stem.1833
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells Prevent T-Cell Activation by Suppressing Dendritic Cells Function via TGF-Beta Signaling Pathway

Abstract: Human embryonic stem cells (hESCs) represent a potential source of transplantable cells for regenerative medicine, but development of teratoma even in syngenic recipients represents a critical obstacle to safe stem cell-based therapies. We hypothesized that hESCs escape the immune surveillance by regulating the environmental immune system. Using cocultures of hESCs with allogenic peripheral blood mononuclear cells, we demonstrated that hESCs prevent proliferation and activation of human CD41 T lymphocytes, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…While some reports have described TGF-β1’s role as a monocyte and macrophage chemoattractant [34, 35], we observed significant decreases in these same myeloid lineage cells that suggests protein delivery blocks migration of these populations or inhibits their local proliferation. TGF-β1 is also known to promote immature and tolerogenic phenotypes on APCs [16, 37–39], which is consistent with the observed decreases in MHCII expression on APC populations. Despite the in vitro release assay data indicating that the majority of TGF-β1 was released within the initial 3 days, leukocyte infiltration was reduced for up to 14 days (Sup.…”
Section: Discussionsupporting
confidence: 75%
“…While some reports have described TGF-β1’s role as a monocyte and macrophage chemoattractant [34, 35], we observed significant decreases in these same myeloid lineage cells that suggests protein delivery blocks migration of these populations or inhibits their local proliferation. TGF-β1 is also known to promote immature and tolerogenic phenotypes on APCs [16, 37–39], which is consistent with the observed decreases in MHCII expression on APC populations. Despite the in vitro release assay data indicating that the majority of TGF-β1 was released within the initial 3 days, leukocyte infiltration was reduced for up to 14 days (Sup.…”
Section: Discussionsupporting
confidence: 75%
“…Platelet-derived IL-1 stimulates cytokine production of vascular smooth muscle cells, indicating that it may regulate cytokine networks during tissue repair processes. [388] PRP has anti-inflammatory, chondroprotective, and potential regenerative properties stimulated when TGF-β, PDGF, EGF, VEGF, FGF, and IGF are released upon de-granulation. Overexpression of TGF-β, however, can also lead to fibrosis [386] and tumor development, [387] and it has crucial roles to play in the regulation of stem and T-cell differentiation.…”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…Overexpression of TGF-β, however, can also lead to fibrosis [386] and tumor development, [387] and it has crucial roles to play in the regulation of stem and T-cell differentiation. [388] PRP has anti-inflammatory, chondroprotective, and potential regenerative properties stimulated when TGF-β, PDGF, EGF, VEGF, FGF, and IGF are released upon de-granulation. These growth factors stimulate cartilage regeneration [389] and inhibit the actions of inflammatory mediators such as IL-1β .…”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…Mesenchymal stem cells 36 38 and NSPCs 39 also exhibit similar immunosuppressive effects. An immunosuppressive effect on surrounding microglia mediated by TGFβ was found in NSPCs 13 , 40 and ESCs 29 . The addition of a TGFβ-neutralizing antibody markedly increased CPM and SI in both fetus-NSPCs and iPSC-NSPCs, suggesting that iPSC-NSPCs exhibit TGFβ-dependent immunomodulatory activity.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported that transforming growth factor β(TGFβ) exerts an immunosuppressive effect in NSPCs 27 , 29 ; thus, we investigated the effects of treatment with a TGFβ-neutralizing antibody 30 . The CPM and SI significantly increased in fetus-NSPCs and 2A4F iPSC-NSPCs after treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%